2002
DOI: 10.1590/s0004-27492002000100018
|View full text |Cite
|
Sign up to set email alerts
|

Indicações de transplante de córnea no Hospital de Clínicas de Porto Alegre

Abstract: Arq Bras Oftalmol 2002;65: Objetivo: Definir as indicações mais freqüentes de ceratoplastia penetrante no Serviço de Oftalmologia da Universidade Federal do Rio Grande do Sul -a verificação da doença corneana mais transplantada bem como as médias etária e de tempo de preservação das córneas utilizadas. Métodos: Foi realizado um estudo retrospectivo comparativo entre os pacientes atendidos e que tiveram indicação de transplante de córnea (transplantados e em lista de espera) no período de janeiro de 1988 a dez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1
27

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 8 publications
3
6
1
27
Order By: Relevance
“…The indications for retransplantation were: irregular astigmatism in 7 (46.6%) eyes, post-refractive surgery in 2 (13.3%), rejection in 4 (26.6%), endothelial failure after transplantation in 1 (6.6%), and post-phakectomy in 1 (6.6%). Other studies found varying rates of retransplantation, some of them similar to our study: 10.1% (4) , 9.8% (5) 13.5% (7) , 12.8% (9) , and 11% (14) . Thanks to improved preservation of corneas, new immunosuppressive drugs, and modifications in surgical techniques, there are now improved prospects for the management of corneal retransplantation.…”
Section: Dendrogram Of Variablessupporting
confidence: 89%
See 2 more Smart Citations
“…The indications for retransplantation were: irregular astigmatism in 7 (46.6%) eyes, post-refractive surgery in 2 (13.3%), rejection in 4 (26.6%), endothelial failure after transplantation in 1 (6.6%), and post-phakectomy in 1 (6.6%). Other studies found varying rates of retransplantation, some of them similar to our study: 10.1% (4) , 9.8% (5) 13.5% (7) , 12.8% (9) , and 11% (14) . Thanks to improved preservation of corneas, new immunosuppressive drugs, and modifications in surgical techniques, there are now improved prospects for the management of corneal retransplantation.…”
Section: Dendrogram Of Variablessupporting
confidence: 89%
“…This is higher than in previous studies, which found rates of 0.4% (4) , 5.5% (9) and 3.4% (14) . Keratoplasty for post-herpetic leukoma can be avoided if patients receive more efficient anti-viral agents and the population has greater access to health care.…”
Section: Dendrogram Of Variablescontrasting
confidence: 78%
See 1 more Smart Citation
“…Visão de vultos e PL (IV) foi a acuidade visual mais freqüente, seguida por "não-disponível (VI)", conta dedos (III), "pior que 20/200 e melhor ou igual a 20/400 (II)", amaurose (V) e "melhor ou igual a 20/200 (I)" (χ 2 =272,2 e p<0,001) (Tabela 2 (3,6) , a CBAP foi a doença que mais freqüentemente levou à indicação de ceratoplastia penetrante, correspondendo a 39,1% dos casos. Esse dado apresentou-se de acordo com algumas publicações norteamericanas (8,10) , cuja percentagem varia de 31,5 a 40,9%.…”
Section: Resultsunclassified
“…De um modo geral, nos Estados Unidos, a principal indicação de CP ainda está relacionada a ceratopatia bolhosa do afácico e do pseudofácico (CBAP). Esses dados diferem quando comparados a publicações da Europa, Nova Zelândia e Brasil, onde a maioria dos relatos mostra o ceratocone como a indicação mais freqüente (3)(4)(5)(6)(7)(8)(9) . Analisando-se o perfil epidemiológico dessas duas doenças, pode-se dizer que a CBAP acomete predominantemente pacientes idosos, sendo 75,9 anos a média etária (8,10) .…”
Section: Introductionunclassified